Branding narodowy jako teoria i praktyka. Krytyczna analiza wybranych tekstów na temat marki kraju z lat 1997-2017 - Bojakowski, Waldemar (Uniwersytet Wrocławski, 2020)
The presented dissertation concerns nation branding as a strict communication phenomenon. Followingthe postulates of the post-foundation discourse analysis, it examines how statements about nation brandmanagement were created and reproduced. In this work, I am assuming that every social order is directlyrelated to the discursive conditions of its possibility. In a practical sense, this means that the questionsabout the rationality of nation branding were actually questions about what reality was created by authorswho considered it legitimate to look at nation-states through the prism of a brand. Thus, the theorymentioned in the title of the dissertation is treated by me a set of statements establishing a certainobservable social order in which categories such as state, nation, and national identity took on a new,previously unknown meaning.The most important objective of the dissertation is to describe how the discourse on the nationbranding was constituted, ie how the foundations for thinking about the nation-state as an „object”of branding activities were created and legitimized. The next task is to try to capture the general dynamicsof national branding, which has been subject to both dispersion and sedimentation over the years. In thisaspect, it is important to characterize the theory of nation brand management in the long run, andto determine on this basis what changes took place within this discursive formation. My last goal isa multi-faceted analysis of specific texts on the national brand, in which the social order that interests mewas created and reproduced.
Keywords: branding narodowy; zarządzanie marketingowe; marketing; marki krajowe